Diagnóstico das condições de formação dos professores e do ensino de Química no município de Barretos - Franco, Ana Leonor Santos Junqueira (2006)
This work presents a descriptive and analytic study on chemical education in Barretos (São Paulo). The purpose of the study is mainly to investigate the pedagogic practices in secondary and higher chemistry education and suggest possible intervention strategies. The methodology involved three types of questionnaires: one completed by secondary chemistry teachers, one by undergraduate professors, and one by undergraduate students. The teacher and professor questionnaires asked teachers and professors to provide information about their own education and experience, the resources available to them, subject implementation and classroom practices, and student evaluation. The student questionnaire asked students a variety of questions about themselves, professors' classroom practices, and the resources available to them. Various instructional practices are not used by secondary teachers and professors. Lectures to the whole class are prevalent in both grades. Text-based and centred approaches are the most common practices. This is of great concern in an issues-based world where science and technology have so much impact on society. Using current science-related issues as an integral part of the chemistry course should be strengthened. The students must be capable of discussing, responding to, and acting upon issues as young citizens in our society. The vast majority of secondary teachers reported that equipment and lab facilities are not available. The situation with respect to higher education is better but still far from satisfactory. Professors and undergraduate students reported that the quantity of lab materials, computers, and library materials is insufficient. This situation should be rectified before the cost of updating and replacing the learning resources for chemistry is impossible to achieve. Tests, supplemented by lab assignments, are the heaviest weighted information source for student evaluation in both grades, although they form a larger portion of students' evaluation. Too little emphasis has been placed on alternate evaluation approaches. Steps should be taken to improve on the variety of appraisal practices at the secondary and tertiary level, and teachers and professors should be assisted in developing their own approaches to evaluation.